Laboratory Approach for Characterizing Degraded Shale Material - A. M. Stroisz; M. H. Bhuiyan; N. Agofack; P. R. Cerasi; M. I. Duda (Rock Mechanics and Rock Engineering, 2026)
This research assesses the potential of unpreserved shale core material to provide adequate geophysical characterization, despite its degraded state. Our goal was to reverse degradation processes, focusing on recapturing the in situ saturation state to analyse the fluid's impact on the mechanical and acoustic properties. An extensive testing program was conducted on various sample saturation states, including unconfined compressive strength, scratch, and punch tests, alongside continuous wave and through-transmission methods. For validation, these were paralleled with tests on preserved material of similar properties, that was deliberately degraded to replicate a poor preservation state in a controlled manner. Our findings reveal that even unpreserved or degraded shale cores can yield valuable data, offering insights into in situ properties through simple, low-cost testing methods, which are particularly effective in cases where preparing standard-size testing plugs is unfeasible. However, fully recovering the in situ properties of an unpreserved shale remain a challenge. The results highlight the need for more controlled research to evaluate the chemical and mechanical impacts on unpreserved shales. Developing methods to accurately reverse core damage, caused by inappropriate preservation, and enhance testing reliability require exploring a broader range of shale samples. This research lays the groundwork for refining approaches to restore and understand the true characteristics of shales, moving closer to replicating the in situ state despite existing challenges.